2021
DOI: 10.1002/fsn3.2598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omega‐3 fatty acids supplementation on indirect blood markers of exercise‐induced muscle damage: Systematic review and meta‐analysis of randomized controlled trials

Abstract: Damaged muscle cells start a reactions cascade that leads to a complicated and prolonged interaction between protein synthesis and degradation (Shen et al., 2018). Therewith, while protein turnover is increased, generally degradation exceeds synthesis, since the breakdown of protein results, leading to muscle atrophy, muscle degeneration, and exercise-induced muscle damage (EIMD; Damas et al., 2016). Exercise-induced muscle damage lead to alteration in muscle protein structure, reductions in muscle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
1
2
1
Order By: Relevance
“…Although mean values for serum CK concentrations were markedly lower in FO than PLA on days 2 (−586 μg/L) and 3 (−719 μg/L) post exercise (Figure 2), these differences did not reach statistical significance when expressed over time or as cumulative AUC. This observation contrasts with a recent meta-analysis conducted in untrained males that revealed FO supplementation attenuated the rise in various blood biomarkers of muscle damage, including CK, myoglobin, and LDH (Xin & Eshaghi, 2021). Taken together, these findings indicate the protective action of Ω3-PUFA in ameliorating EIMD may be specific to untrained individuals who experience a greater severity of myofibrillar disruption given the unaccustomed nature of exercise.…”
Section: Discussioncontrasting
confidence: 90%
“…Although mean values for serum CK concentrations were markedly lower in FO than PLA on days 2 (−586 μg/L) and 3 (−719 μg/L) post exercise (Figure 2), these differences did not reach statistical significance when expressed over time or as cumulative AUC. This observation contrasts with a recent meta-analysis conducted in untrained males that revealed FO supplementation attenuated the rise in various blood biomarkers of muscle damage, including CK, myoglobin, and LDH (Xin & Eshaghi, 2021). Taken together, these findings indicate the protective action of Ω3-PUFA in ameliorating EIMD may be specific to untrained individuals who experience a greater severity of myofibrillar disruption given the unaccustomed nature of exercise.…”
Section: Discussioncontrasting
confidence: 90%
“…However, according to [51,52], only some of the ASD patients with mitochondrial dysfunction had elevated CK levels. The significantly lower CK reported in rats fed fish (Figure 3A) could find support in the previous study of [53] who showed that ω-3 was effective in lowering CK and LDH serum levels in healthy persons. Therefore, ω-3 should be prioritised as a recovery agent for exercise-induced muscle damage in therapies.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, Kyriakidou et al [ 102 ] showed that 4 weeks of n-3 PUFA supplementation successfully attenuated minor aspects of EIMD, although it did not improve performance. Recent systematic reviews and meta-analyses have corroborated the efficacy of n-3 PUFAs in reducing DOMS and markers of muscle damage [ 103 , 104 ]; however, only a few studies have found significantly lower maximal muscle strength loss or recovery (i.e., maximal voluntary contraction; MVC), indicated as the best indirect marker of muscle damage, probably because of a poor control of the participants’ diet characteristics affecting the n-6/n-3 ratio and the use of a broad range of supplementation doses and times. Therefore, more studies assessing MVC after damage are warranted.…”
Section: Clinical Interventions Supporting the Consumption Of N-3 Puf...mentioning
confidence: 99%